2002
DOI: 10.1002/hfm.10010
|View full text |Cite
|
Sign up to set email alerts
|

An expert cognitive approach to evaluate physical effort and injury risk in manual lifting—A brief report of a pilot study

Abstract: Although the development of the National Institute for Occupational Safety and Health (NIOSH) equation was partly based on the expertise of committee members convened under the auspices of NIOSH, to our knowledge, there is no study reported in the published literature that examined the role of professional expertise in determining the relative contribution of different lifting task variables to effort exertion. In this study, we explored whether professional expertise can be relied on, through the use of a sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 10 publications
3
9
0
2
Order By: Relevance
“…Genaidy and coworkers (Genaidy et al 1990(Genaidy et al /2000Yeung et al 2001) found that the weight of load was regarded as the liftingtask parameter that possessed the greatest effect on perceived effort and perceived risk of injury, followed by other lifting variables. These findings are in agreement with those of (1) a survey conducted by the US Bureau of Labor Statistics (1982) on back injuries sustained by 900 workers in blue-collar jobs while lifting, placing, carrying, holding or lowering objects and (2) Yeung et al (2002b), who used a similar approach on expert professionals. The object weight was the most frequently cited factor by workers at the time of the injury in the US Bureau of Labor Statistics Report (1982).…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Genaidy and coworkers (Genaidy et al 1990(Genaidy et al /2000Yeung et al 2001) found that the weight of load was regarded as the liftingtask parameter that possessed the greatest effect on perceived effort and perceived risk of injury, followed by other lifting variables. These findings are in agreement with those of (1) a survey conducted by the US Bureau of Labor Statistics (1982) on back injuries sustained by 900 workers in blue-collar jobs while lifting, placing, carrying, holding or lowering objects and (2) Yeung et al (2002b), who used a similar approach on expert professionals. The object weight was the most frequently cited factor by workers at the time of the injury in the US Bureau of Labor Statistics Report (1982).…”
Section: Introductionsupporting
confidence: 92%
“…The object weight was the most frequently cited factor by workers at the time of the injury in the US Bureau of Labor Statistics Report (1982). In the study by Yeung et al (2002b), each of their expert professionals consistently determined weight as being the variable that produced the largest effect on effort associated with the performance of manual-handling activities. The findings of Yeung et al on expert professionals agree with those of Genaidy et al (1999Genaidy et al ( /2000 on expert workers in that other lifting-task variables were not substantially different in terms of their effect on effort.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, manual material handling (MMH) tasks are of great signiÞcance from two aspects. First, according to the surveys, approximately one third of all industrial jobs are associated with some form of MMH task such as lifting, lowering, holding, carrying, pushing or pulling (Konz, 1995); and, second, there is strong evidence that MMH tasks are the leading cause of low back disorders (LBDs) (Bernard, 1997;Kuiper, Burdorf, Verbeek, Fringes-Dresen, van der Beek, & Viikari-Juntura, 1999;Yeung, Genaidy, Huston, & Karwowski, 2002) representing the most common and most costly musculoskeletal disorder experienced in the workplace (Marras, 2000). According to the statistics, up to 80% of people experience back pain during their lifetime and 4 ± 5% of the population has an acute low back pain experience every year (Plante, Rothwell, & Tufo, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It has been broadly estimated that more than a quarter of all injuries related to industrial work are directly or indirectly associated with MMH activities (Konz, 1995). Physical efforts that are involved and the risk of injury during manual lifting tasks had been reported based on a pilot study using an expert cognitive approach (Yeung, Genaidy, Huston, & Karwowski, 2002). Effective ergonomic interventions can lower injury risk due to MMH tasks.…”
Section: Introductionmentioning
confidence: 99%